"The Mill on the Floss" - the critique of the concept of education in Victorian Great Britain - Ninčetović, Nataša V. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2021)
George  Eliot  was  not  only  a  significant  Victorian  writer, but  primarily   an  intellectual. She thought  that  literature  had  an  important  role   in  the  reform  of  society, the moral  and  educational  function. Eliot  interwove  her  views  on  the direction  in  which  the  society  should  move  in  her  works, so  that  the  analysis  of  her  opus  cannot  be  separated  from  the  social  circumstances  in  Victorian  Great  Britain. The  aim  of  this  work  is  to  imply at  the  fact  that  by  means  of  The  Mill  on  the  Floss  George Eliot indirectly criticized  the  official  concept  of  education  of  the  Victorian  era. The  starting  point  of  our  research  is  an  overview  of   the  state  of  society, followed  up  by George  Eliot's  attitudes  towards  the  question  of  education, which  can  be  found  in  her  essays  and  letters. The  Mill  on  the  Floss is  a  picturesque  illustration  of  George  Eliot's  beliefs  that  education  should  be  reformed, as  well  as  of  the  need  of  a  different  approach  to  this  extremely  important  question. The  implication  of  this  novel  is  that  education  needs  to  be  appropriate  to  the  requisites  and  competences  of  the  student, but  also  that  education  mustn't  be  reduced   to  a commodity, so  that  we  should  raise  the  awareness  that  education  has  a  much  more  important  and  wider  role  than mere acquisition  of  a  degree  and  means  that  will  faciliate  easier  employment.
Keywords: education; commodity; individuality; women's education; guidance